Advances on materials design and manufacture technology of plastic liner of type Ⅳ hydrogen storage vessel. (12th February 2022) - Wang, Xiulei; Tian, Mingming; Chen, Xuedong; Xie, Pengcheng; Yang, Jianing; Chen, Junxiang; Yang, Weimin
Abstract: The growing demand for type IV hydrogen tanks with long life, lightweight, high hydrogen storage density characteristics has posed new issues for liners. The paper discusses the causes of liner failure in terms of hydrogen permeation, thermal instability, and mechanical damage, as well as a focused analysis of alternative material optimization strategies. Through a detailed investigation of aggregate state structures, formulations and processes, the principles of material modification, primarily inorganic functional filler/polymer filler filling composite and laminated orientation, and their enhancing effects are sorted out. Besides, the benefits and drawbacks of blow molding, injection and welding, and the rotating technique, which were employed by some manufacturers are contrasted in the article, for overcome the problematic molding of hollow plastic liners with metal BOSS structures. This text will be a valuable resource for material exploitation as well as efficient and reliable molding of various liners. Highlights: Improve hydrogen storage density and application range by material modification. The failure modes of the plastic liner material are discussed. Hydrogen barrier, mechanical and thermal properties modify measures were reviewed. Molding methods for synthetic liners containing metal inserts are compared. The recommendations for future liner materials design and molding are presented.